2011
DOI: 10.1002/pro.678
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition influences the release of Alzheimer's amyloid β‐peptide from membranes

Abstract: The behavior of the amyloid b-peptide (Ab) within a membrane environment is integral to its toxicity and the progression of Alzheimer's disease. Ganglioside GM1 has been shown to enhance the aggregation of Ab, but the underlying mechanism is unknown. Using atomistic molecular dynamics simulations, we explored the interactions between the 40-residue alloform of Ab (Ab 40 ) and several model membranes, including pure palmitoyloleoylphosphatidylcholine (POPC) and palmitoyloleoylphosphatidylserine (POPS), an equim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 67 publications
10
81
1
Order By: Relevance
“…The anchoring of the Aß C-terminus to the cytofacial membrane interface has been seen in some simulations 24,26 but other conformations are common. Simulations addressing inserted Aß as the initial state show a wide range of behavior from anchoring to the extracellular membrane interface, 24,27,28 to ejection from the membrane.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The anchoring of the Aß C-terminus to the cytofacial membrane interface has been seen in some simulations 24,26 but other conformations are common. Simulations addressing inserted Aß as the initial state show a wide range of behavior from anchoring to the extracellular membrane interface, 24,27,28 to ejection from the membrane.…”
Section: Discussionmentioning
confidence: 96%
“…Simulations addressing inserted Aß as the initial state show a wide range of behavior from anchoring to the extracellular membrane interface, 24,27,28 to ejection from the membrane. 26,31 However, few simulations 26 have addressed Aß interactions with membranes composed of CHOL and unsaturated lipids. Indeed, we see anchoring in only 3 of 8 cases for membranes that do not contain CHOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modifi cations in GP compositions may change cell membrane fl uidity, alter amyloid precursor protein processing, and infl uence the release of neurotoxic A ␤ 42 ( 49,50 ). An increase in PLA 2 activity combined with the higher LPC/PC in CSF is evidence of neuroinfl ammation in LOAD.…”
Section: Role Of Gp Metabolism In Clinical Groupsmentioning
confidence: 99%
“…Increased BACE1-mediated ␤APP cleavage also led to an increased release of ␤APP intracellular fragment AICD, which downregulated low-density lipoprotein-related protein 1 (LRP-1) transcription and decreased the amount of LRP1 receptor responsible for exogenous cholesterol capture at the plasma membrane [51]. It was shown that lowering cholesterol levels by statins and methyl-␤-cyclodextrine (M␤CD), respectively, reduced intracellular and extracellular levels of A␤ 40 and A␤ 42 in cultured neurons [49,52,53], suggesting that amyloidogenesis process is affected by cholesterol composition in lipid rafts [54].…”
Section: Cholesterol In Admentioning
confidence: 99%